A Facile Synthesis of Poly(3‐octyl thiophene):Ni0.4Sr0.6TiO3 Hybrid Nanocomposites for Solar Cell Applications. Issue 1 (19th August 2020) - Adimule, Vinayak; Suryavanshi, Anusha; BC, Yallur; Nandi, Santosh S.
Abstract: The solar cell properties of poly(3‐octyl thiophene) (P3OT) doped with Ni0.4 Sr0.6 TiO3 nanocomposite (NCs) as a function of P3OT in different concentrations are studied for photovoltaic characteristics using Hg probe instrumental technique without any fabrication. Nickel nanoparticles (Ni + ) loaded with SrTiO3 nanoparticles are attempted to be synthesized by co‐precipitation method, cetyl trimethyl ammonium bromide is used as capping agent and is successfully converted into Ni‐SrTiO3 hybrid nanoparticles. The thin films are made by using different solvent systems in spin coating method, for low concentration (20–30%) of P3OT the device performance is poor compared to pure Ni‐SrTiO3 . Significant improvements are obtained with the increased doping (50%) of P3OT. The maximum absorbance in the thin film of UV spectrum lies between 600 and 800 nm spectral region. Increased addition of P3OT results UV band shifts in visible spectral region while power conversion efficiency increases approximately ten times than the existing. The increased solar cell efficiency is strongly dependent not only on the doping of P3OT concentration but also on the solvent used, changes in the film morphology. The optimal fabrication the external quantum efficiency of 10% and power conversion efficiency of 17.12% were obtained.